Faktor-Faktor yang Berhubungan dengan Terjadinya Ketuban Pecah Dini (KPD) di Rumah Sakit Muhammadiyah Palembang Tahun 2021 - Nani Widia; Yulizar Yulizar; Merisa Riski (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
WHO said cases of premature rupture of membranes ± 5-10% of the total births. PROM in preterm cases is 1% and term pregnancies are 22% of the total pregnancies. Premature rupture of membranes is the rupture of the membranes before the time of delivery that occurs at the end of pregnancy or before. Factors causing PROM are divided into general factors, heredity factors, and obstetric factors. This study aims to determine the relationship between fetal position abnormalities, multiple pregnancies, parity and infection with premature rupture of membranes at Palembang Muhammadiyah Hospital in 2021. Analytical survey research with a Cross Sectional approach. All mothers giving birth at term who were treated at the Palembang Muhammadiyah Hospital in January-May 2021, totaling 965 were used as the population and a sample of 91 mothers were taken using simple random sampling technique. The primary data used was then analyzed by univariate and bivariate analysis by chi square test. The results showed that there was a relationship between fetal position abnormalities (Pvalue = 0.031), multiple pregnancy (Pvalue = 0.001), parity (Pvalue = 0.031) and infection (Pvalue = 0.018) with premature rupture of membranes at Muhammadiyah Hospital Palembang in 2021. It is expected from the results of the study. This can be an illustration for the hospital to further improve health services, especially dealing with the incidence of premature rupture of membranes.